Validation of Parenting Styles and Dimensions Questionnaire (PSDQ) on Adolescents - Siti Atiyyatul Fahiroh; Mareyke M.W. Tairas; Sofia Retnowati (Universitas Ahmad Dahlan, 2019)
AbstractÂ The objective of this study is to determine the validity and reliability level of Parenting Styles and Dimensions Questionnaire (PSDQ) on adolescents in Senior High School of Surabaya city. Participants consisted of 204 students of Senior High School from several regions in Surabaya. They were between 16 and 19 years old. Confirmatory Factors Analysis (CFA) was used for the Parenting Styles and Dimensions Questionnaire (PSDQ) of Robinson, at all (1995). From 62 items in this measurement found 52 items that meet the validity requirements for father's parenting measurement and 52 items that meet the validity requirements for mother's parenting measurement.Â Keywords: Parenting styles, psychometric validation, adolescence.